1996
DOI: 10.1177/001698629604000402
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Academic Intrinsic Motivation in Intellectually Gifted Children: Childhood Through Early Adolescence

Abstract: Academic intrinsic motivation of intellectually gifted children and a comparison group was examined in the Fullerton Longitudinal Study. Children at ages 9 through 13 years were administered the Children's Academic Intrinsic Motivation Inventory which assesses intrinsic motivation for school learning in reading, math, social studies, science, and for school in general. Analyses showed that across the ages, relative to a peer comparison, gifted children had significantly higher academic intrinsic motivation acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 15 publications
5
72
0
1
Order By: Relevance
“…A substantial body of research (e.g. Dweck, 2002;Eccles, Roeser, Wigfield, & Freedman-Doan, 1999) has been devoted to the identification of specific aspects of and factors contributing to engagement under the assumption that the link between engagement and school performance (Gottfried & Gottfried, 1996) is independent of academic ability or intelligence. This assumption has been tested, but only relatively rarely (e.g., Aspinwall & Taylor, 1992;Gagne & St. Pere, 2001;Lloyd & Barenblatt, 1984).…”
Section: The Role Of Engagement In School Performancementioning
confidence: 99%
“…A substantial body of research (e.g. Dweck, 2002;Eccles, Roeser, Wigfield, & Freedman-Doan, 1999) has been devoted to the identification of specific aspects of and factors contributing to engagement under the assumption that the link between engagement and school performance (Gottfried & Gottfried, 1996) is independent of academic ability or intelligence. This assumption has been tested, but only relatively rarely (e.g., Aspinwall & Taylor, 1992;Gagne & St. Pere, 2001;Lloyd & Barenblatt, 1984).…”
Section: The Role Of Engagement In School Performancementioning
confidence: 99%
“…From the elementary through the junior high school years, academic intrinsic motivation has been shown to be positively and significantly related to students' achievement and perception of their academic competence, and inversely related to their academic anxiety (A. E. Gottfried, 1985(A. E. Gottfried, , 1986a(A. E. Gottfried, , 1990. Moreover, longitudinal studies of academic intrinsic motivation have shown continuity of the construct over time during childhood and early adolescence (A. E. Gottfried, 1990; A. E. Gottfried, Fleming, & A. W. Gottfried, 1994; A. E. Gottfried & A. W. Gottfried, 1996). The present study focuses on the role of home environment, specifically, cognitively stimulating home environment, in the development of academic intrinsic motivation in a longitudinal study from childhood through early adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Because Hortsmanshof and Zimitat (2007) argued that future-oriented students are more intrinsically motivated. Furthermore, gifted students scored more intrinsically than other students on measures of motivation in many research (Csikszentmihalyi, Rathunde, & Whalen, 1993;Gottfried & Gottfried 1996;OlszewskiKubilius, Kulieke, & Krasney, 1988). Correlation between hopelessness scale and positive future expectations scale was found as r=-.45.…”
Section: Discussionmentioning
confidence: 99%